Migration and infectious disease risk: knowledge and perception among university students in two European countries - Marconi, Domitilla; Casigliani, Virginia; Mazzilli, Sara; Tavoschi, Lara; Lopalco, Pier Luigi (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. In the past years, migration has increasingly affected the European continent. The concerns of the local population about infection spread by migrants may increase as an unjustified stigma. Our study aimed to assess the knowledge and risk perception of infectious disease associated with migration among university students. Methods. Between January and February 2020, we conducted an online survey in Italian and Spanish University students. We collected data on demographics, perception, and knowledge of infectious diseases associated with migration. We performed descriptive and risk factors analysis to assess the association among selected variables. Results. We collected 1,397 answers, 73.16% from Italian students and 26.84% from Spanish students, 34.54% and 38.67% enrolled in healthcare degrees, respectively. We found a statistically significant correlation between the knowledge of infectious diseases and the perception of the infectious risk associated with migration, not confirmed for the area of study. Healthcare students had the best levels of knowledge and perception of the migratory phenomenon, but the higher perception of infectious risk. Exposure to the media coverage about migration was associated with the worst perception of the migratory phenomenon and infectious risk. Conclusion. Our study showed that, despite healthcare students had the best levels of knowledge, they had the highest risk perception of infectious diseases associated with migration. The inclusion of courses on migration medicine in current healthcare curricula and the increase of practical training could help to avoid the development of biased approaches towards migrants among healthcare professionals.